THE USE OF CORPORATE DERIVATIVE INSTRUMENTS IN FACING CRISES IN INDONESIA - Syafri, Muhammad; Rijal, Syamsu; Munizu, Musran; Sudarmanto, Eko; Nanda, Sahabuddin (Multifinance, 2023)
This research aims to analyze the company's use of derivative instruments in facing the crisis. The research method is qualitative research a research method used to understand social phenomena in depth. This type of research is library research which researchers carry out by collecting, studying and analyzing references or sources. obtained in writing or written form such as books, journals, articles, documents and other sources of information that are significant to the topic/title being researched. The research results show that the use of derivative instruments by companies in facing a crisis is an important strategy to protect asset value, manage risk and maintain business continuity. Derivative instruments can provide significant benefits, such as hedging against price or exchange rate fluctuations, better risk management, additional access to liquidity, and portfolio diversification.